Executive functions in primary progressive aphasia: A meta-analysis. (December 2022) - Coemans, Silke; Keulen, Stefanie; Savieri, Perseverence; Tsapkini, Kyrana; Engelborghs, Sebastiaan; Chrispeels, Nini; Vandenborre, Dorien; Paquier, Philippe; Wilssens, Ineke; Declerck, Mathieu; Struys, Esli
Abstract: Executive functions (EFs) refer to a set of cognitive processes, specifically shifting, inhibition, updating of working memory, and are involved in the cognitive control of behavior. Conflicting results have been reported regarding impairments of EFs in Primary Progressive Aphasia (PPA). We performed a multi-level meta-analysis to confirm whether deficits of EFs exist in this population, focusing on a common EFs composite, and the components shifting, inhibition and updating separately. We included 141 studies that report on 294 EFs tasks. The overall mean weighted effect size was large ( d = −1, 28), indicating poorer EFs in PPA as compared to age-matched cognitively healthy controls. Differences between effect sizes of the EFs components were not significant, indicating all components are affected similarly. Overall, moderator analysis revealed that PPA variant and disease duration were significant moderators of performance, while task modality and years of education were not. The non-fluent/agrammatic PPA and the logopenic PPA variants were similarly affected, but the semantic variant was affected to a lesser extent. We discuss implications for clinical and research settings, and future research.